Editorial: New Conversations in Islamic and Christian Political Thought - Hordern, J; al-Akiti, A (SAGE Publications, 2016)
The focus of this project, New Conversations in Islamic and Christian Political Thought, concerns the ‘pre-modern’ or ‘long’ traditions of political thought in Islam and Christianity. The renaissance in Christian political thought since World War II has not yet witnessed a sustained engagement with Islamic political thought. Meanwhile, the interface of religion and political life has increasingly become a major focus of academic and public discourse. By exploring the varied traditions of Islam and Christianity, this project seeks to retrieve and develop wisdom in political understanding with a view to enriching this discourse.